The mediating role of personal values between COVID-19-related posttraumatic growth and life satisfaction among Chinese college students: A two-wave longitudinal study - Xie, Jia-Qiong; Zhang, Hua; Zhang, Xiang; Yin, Ming-Ze; Yang, Jing; Chen, Ke; Xiong, Jian-Ru; Chen, Yi-Qiang (Frontiers in Psychology, 2022)
Despite considerable disruption of social order caused by the COVID-19 pandemic, it has also been said to contribute to positive psychological changes and influence on the perception of public life satisfaction. The present study aimed to explore the association between the COVID-19 related posttraumatic growth and life satisfaction and the mediating role of personal values. A two-wave longitudinal design was used. 226 self-quarantined Chinese college students (58.8% male) completed post traumatic growth inventory (Time 1), satisfaction with life scale (Time 2), personal values questionnaire (Time 2) between February 2020 and May 2021. Results showed that more than half of self-quarantined Chinese college students reported moderate to high levels of the COVID-19 related posttraumatic growth. A structural equation model revealed that COVID-19 related posttraumatic growth was positively associated to life satisfaction, and self-transcendence and self-enhancement values partially mediated this association. These findings shed light on whether and how pandemic-related posttraumatic growth influenced personal life satisfaction, supporting the outcome and process perspectives of posttraumatic growth as well as Schwartz’s value theory. Based on the findings, some positive psychology interventions, such as online rumination activities and mindfulness practice, were proposed to enhance self-quarantined college students’ posttraumatic growth and life satisfaction.